THE ROLE OF THE WEST JAVA PROVINCE DPRD IN SUPERVISION - Dea Eka Rizaldi; Ade Maman Suherman; Tri Setiady; Wiwin Triyunarti (Program Studi Hukum Fakultas Hukum Universitas Buana Perjuangan Karawang, 2026)
The context of West Java Province is interesting to study in depthbecause its complex characteristics in terms of population,budget allocation, and diversity of sectoral issues require a stronger and more adaptive oversight mechanismthan other regions. To achievethese objectives, this study will use a comparative qualitative research designand document analysis, in-depth interviews, and case studies. Overall, the DPRD oversight mechanism in Indonesia has a fairlycomplete set of normative instruments, but its effectiveness is still influenced by internal factorssuch as the political and regulatory capacity of council members, as well as external factorssuch as executive transparency and public participation. Therefore, increasing legislative professionalism and inter-institutional synergy is animportant agenda for strengthening local government accountability. Finally, public participation and local media play a reinforcing role in thelegislative oversight mechanism. Support from civil society, non-governmental organizations(NGOs), and regional media can increase public pressurefor the DPRD to carry out its control function more firmly and openly. A responsive public complaint mechanismcan also be an effective channel foridentifying policy irregularities at the local level. However, several reinforcing factors such as budget transparency, the role of external (BPK) andinternal audits, as well as public and media participation can encourage improvements in thequality of oversight. In the context of West Java, which is highly complexand covers a large area, DPRD oversight has a positive influence onthe accountability of regional heads, although there is still a gap between regulatory normsand implementation practices in the field. Translated with DeepL.com (free version)